EFEKTIVITAS PELAYANAN SILASEMEDI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Nurhayati, Tuti (JRPA - Journal of Regional Public Administration, 2025)
This study aims to determine the effectiveness of the One-Day Service System (SILASEMEDI) at the Department of Population and Civil Registration of Sumedang Regency, as well as to identify the inhibiting factors and efforts made to overcome them. SILASEMEDI is a public service innovation designed to accelerate the process of population administration through offline, online, and mobile services. This research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The results of the study indicate that although SILASEMEDI provides convenience and service acceleration for the community, its implementation has not been fully effective. The main obstacles include limited human resources, working hours that are not proportional to the number of applicants, and inadequate network infrastructure, especially in remote areas. Efforts made include adjusting service schedules, utilizing information technology, and strengthening the capacity of civil servants. This study recommends the addition of personnel, improvement of staff competencies, and strengthening of facilities and infrastructure to enhance service effectiveness. Thus, SILASEMEDI can be more optimal in providing fast, accurate, and satisfactory population administration services to the public. Keywords: Effectivensess, One-Day Service System